Analisis Penerapan E-learning Menggunakan Thechnology Acceptance Model (TAM) - Idria Maita; Almarozi (Jurnal Informasi dan Teknologi, 2022)
Senior High Schools in the Pekanbaru area have utilized E-learning facilities during the Covid-19 pandemic. One type of E-learning used is Edmodo-based. Factors that hinder the implementation of Edmodo-based E-learning are that students do not understand the use of Edmodo-based E-learning, not all teachers use Edmodo-based E-learning in schools, and not all students are or live in places that have a good or stable network so that there is no research that leads or leads to aspects of the ease, benefits and acceptance of Edmodo-based E-learning. The purpose of this study is to analyze and determine the effect of usefulness or benefits and perceptions of ease of use on the acceptance of Edmodo-based E-learning at SMA N 12 Pekanbaru using the TAM method. There are three variables used in this study, namely Perception of Ease and Perception of Benefits on Perception of Acceptance of Use. The sample used was 76 respondents. From the results of the assessment and testing, it can be concluded that the three hypotheses proposed are accepted. The convenience variable affects Edmodo Elearning Acceptance, the Benefit variable affects Edmodo Elearning Acceptance and the convenience and benefits variables together affect Edmodo Elearning Acceptance. The more the ease and usability or the benefits of Edmodo E-learning, the more Edmodo's acceptance of E-learning will increase.